Combination of Metformin and Magnesium Citrate Reduces TNF-α, NF-κB p65, IL-6, CD4, and MMP-9 Expressions in Diabetic Model Rats - Rachmi Fauziah Rahayu; Adi Prayitno; Bambang Purwanto; Widiastuti Soewondo; Ida Nurwati; Eti Poncorini Pamungkasari; Paramasari Dirgahayu (The Prodia Education and Research Institute (PERI), 2024)
BACKGROUND: Diabetes, which causes various complications, involves pro-inflammatory cytokines such as tumor necrosis factor-alpha (TNF-α), nuclear factor kappa B p65 (NF-κB p65), interleukin-6 (IL-6), cluster of differentiation 4 (CD4), and matrix metalloproteinase-9 (MMP-9). Magnesium has demonstrated anti-diabetic properties, but its anti-inflammatory effects in preventing cardiovascular complications remain unclear. This study aimed to evaluate the anti-inflammatory effects of magnesium citrate, alone and in combination with metformin, by measuring TNF-α, NF-κB p65, IL-6, CD4, and MMP-9 expression in diabetic model rats.METHODS: Thirty male Wistar rats were divided into five groups: normal control, diabetes control, metformin (treated with 9 mg/200 g/day metformin), magnesium citrate (treated with 3.6 mg/200 g/day magnesium citrate), and combination therapy (treated with 4.5 mg/200 g/day metformin + 1.8 mg/200 g/day magnesium citrate). Diabetes was induced in all groups except the normal control group using streptozotocin (STZ) and nicotinamide (NA). TNF-α, NF-κB p65, IL-6, CD4, and MMP-9 expression levels were measured using enzyme-linked immunosorbent assay (ELISA).RESULTS: Significant differences in TNF-α, NF-κB p65, IL-6, CD4, and MMP-9 expression levels were observed across all groups (p<0.001). The combination therapy group demonstrated the most significant reduction in all parameters compared to the diabetic control group (p<0.001) and other therapy groups. Both metformin and magnesium citrate monotherapies showed moderate reductions in cytokine levels but were less effective than combination therapy.CONCLUSION: Combination therapy with metformin and magnesium citrate exhibited the most potent anti-inflammatory effects, significantly reducing TNF-α, NF-κB p65, IL-6, CD4, and MMP-9 expressions in diabetic Wistar rats. This combination has potential as a therapeutic approach for managing diabetes and its complications.KEYWORDS: diabetes mellitus, inflammation, cytokines, metformin, magnesium citrate